THE IMPLEMENTATION OF CASH WAQF IN THE PESANTREN OF AL-AMIEN PRENDUAN SUMENEP REGENCY OF MADURA - Moch. Cholid Wardi (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2016)
Abstract:Cash waqf still becomes the frame in the ulama’ debate, especially in Hanafiyah and Syâfi`îyah schools. Therefore, it requires deeper insight either empirically from the field or theoritically in Islamic law analysis through aqwâl al-`ulamâ’, so that the concept and the legal basis of its management and development can be known. This paper discusses about productive waqf and the uniqueness of the application of management of cash waqf in a pesantren (Islamic boarding school). Besides, the standardisation of the law applied in the implementation of the cash waqf which encompasses: al-Qur'an, Hadits, fiqh rules, and aqwâl al-`ulamâ’ needs to be analyzed fo find out a conclusion of the implementation status. In the implementation, there are many unique things which are interesting to analyze, namely the use of the institution fund which is oriented to develop cash waqf and the exictence of waqf board which becomes the highest decision maker. It means that the highest leader is no longer on the foundation but on the waqf board because all of the pesantren’s assets become waqf property, even the body and everything valuable to them are made as waqf assets.Abstrak:Cash waqf atau biasa disebut dengan wakaf tunai ini masih menjadi bingkai dalam perdebatan ulama, lebih-lebih dari golongan Hanafiyah dan Syâfi’îyah. Oleh karenanya, ia perlu digali informasi baik secara empiris di lapangan maupun secara teoritis dalam kajian hukum Islam melalui aqwâl al-`ulamâ’ sehingga dapat diketahui konsep dan dasar hukum yang dipakai dalam pengelolaan dan pengembangannya. Tulisan ini membahas wakaf produktif dan keunikan pelaksanaan manajemen wakaf tunai di pesantren. Di samping itu, standarisasi hukum yang digunakan dalam implementasi perwakafan tunai ini (cash waqf) yang meliputi: al-Qur`ân, Hadits, kaidah fiqhiyah, kaidah ushuliyah, dan aqwâl al-‘ulamâ perlu dikaji untuk menemukan kesimpulan status pelaksanaannya. Dalam implementasinya, beberapa hal unik yang menarik untuk dikaji, yaitu penggunaan dana lembaga yang diorientasikan untuk mengembangkan wakaf tunai. Eksistensi badan wakaf yang menjadi penentu kebijakan tertinggi, artinya pimpinan tertinggi tidak lagi dipegang oleh yayasan, melainkan badan wakaf karena semua aset pesantren dijadikan sebagai harta wakaf, bahkan badan dan sesuatu yang bermanfaat dari diri mereka dijadikan sebagai aset wakaf.